2009
DOI: 10.1071/bt07176
|View full text |Cite
|
Sign up to set email alerts
|

Foliar anatomy of the subfamily Myrtoideae (Myrtaceae)

Abstract: The foliar structure of 44 species of Myrtoideae Nied. (Myrtaceae) was described to characterise the anatomy of the leaves in this subfamily and also to recognise particular features in each genus and/or subtribe. In the present study, nine genera of the subtribe Myrtinae, five genera of the subtribe Myrciinae and eight genera of the subtribe Eugeniinae were examined. All of them have dorsiventral and hypostomatic leaves, with stomata slightly protruded in relation to other epidermal cells; the leaves also pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 18 publications
1
21
1
2
Order By: Relevance
“…Within this genus, Myrcia tomentosa, popularly known as "goiababrava", can be found from Panama, northern Venezuela and Guyana to southeast Brazil (McVaugh, 1969) and is often cited in works on the flora, phytosociology and characterization of the Savanna/Cerrado (Mahmoud et al, 2003;Teixeira et al, 2004;Morais & Lombardi, 2006). However, few works report pharmacognostic or phytochemical studies for this species (Dianese et al, 1993;Cardoso & Sajo, 2006;Rossatto et al, 2009, Cardoso et al, 2009, and no reports have been found concerning its popular use.…”
Section: Introductionmentioning
confidence: 99%
“…Within this genus, Myrcia tomentosa, popularly known as "goiababrava", can be found from Panama, northern Venezuela and Guyana to southeast Brazil (McVaugh, 1969) and is often cited in works on the flora, phytosociology and characterization of the Savanna/Cerrado (Mahmoud et al, 2003;Teixeira et al, 2004;Morais & Lombardi, 2006). However, few works report pharmacognostic or phytochemical studies for this species (Dianese et al, 1993;Cardoso & Sajo, 2006;Rossatto et al, 2009, Cardoso et al, 2009, and no reports have been found concerning its popular use.…”
Section: Introductionmentioning
confidence: 99%
“…Donato and Morretes (2011) reported the same structures for Myrcia multiflora. Polyhedral crystals, including druses, have been reported in Psidium, Eugenia, Gomidesia and Myrcia, among others (Cardoso et al 2009;Gomes et al 2009). The function of these structures is not completely clear but has been related to the regulation of calcium and other minerals (Volk et al 2002), as well as protection against herbivores and pathogens (Franceschi and Nakata 2005; Korth et al 2006).…”
Section: Discussionmentioning
confidence: 97%
“…This character is regarded as a typical anatomical character in the order Myrtales (Cronquist 1981;Takhtajan 1980) and is widely present in Myrtaceae (Schmid 1980;Cardoso al. 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function and adaptive value of anatomical features are often extremely useful as they may help to reveal more clearly the homologies of structures for classification purposes and reconstruction of phylogeny (Stuessy 1990). Structural aspects of some vegetative organs, for example, have contributed to the generic/infrageneric delimitation of many groups (Weiner and Liese 1993, Starr and Ford 2001, Alves et al 2002, Calvente et al 2008, Oliveira et al 2008, Cardoso et al 2009). …”
Section: Introductionmentioning
confidence: 99%